Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1051/0004-6361/200811145
|View full text |Cite
|
Sign up to set email alerts
|

VLBI observations of the CORALZ sample: young radio sources at low redshift

Abstract: Context. Young radio-loud active galactic nuclei form an important tool to investigate the evolution of extragalactic radio sources. To study the early phases of expanding radio sources, we have constructed CORALZ, a sample of 25 compact (θ < 2 ) radio sources associated with nearby (z < 0.16) galaxies. Aims. In this paper we determine the morphologies, linear sizes, and place first constraints on the lobe expansion speeds of the sources in the sample. Methods. We observed the radio sources from the CORALZ sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(112 citation statements)
references
References 35 publications
(75 reference statements)
9
103
0
Order By: Relevance
“…The observed range of spectral indices above the peak for samples of CSS and GPS sources is α = 0.5-0.9 (O'Dea et al 1990), which partially overlaps with the CSO range. The same range was derived for the spectral index above spectra peak for GPS and FR galaxies, suggesting that particle acceleration and energy loss mechanism preserve the same average spectral index over most of the lifetime of the source (de Vries et al 2009). Variability of the spectral index has also been associated with the HFP sources and to identify truly young sources (Orienti et al 2007).…”
Section: Spectral Index Versus Time and Sizesupporting
confidence: 63%
See 1 more Smart Citation
“…The observed range of spectral indices above the peak for samples of CSS and GPS sources is α = 0.5-0.9 (O'Dea et al 1990), which partially overlaps with the CSO range. The same range was derived for the spectral index above spectra peak for GPS and FR galaxies, suggesting that particle acceleration and energy loss mechanism preserve the same average spectral index over most of the lifetime of the source (de Vries et al 2009). Variability of the spectral index has also been associated with the HFP sources and to identify truly young sources (Orienti et al 2007).…”
Section: Spectral Index Versus Time and Sizesupporting
confidence: 63%
“…The current (P rad -D) diagram contains similar but also different groups of data points than earlier versions, particularly for the region of early development of CSO radio sources. A sample of low-power GPS sources (de Vries et al 2009) has been included in the bottom left corner of the diagram as likely precursors of the low-power MSO sources (KunertBajraszewska et al 2010). In addition, there are more data points for the group of low-power FR Is (<10 24 W Hz −1 ; Laing et al 1983;Fanti et al 1987Fanti et al , 2001).…”
Section: Evolution Of the Radio Structurementioning
confidence: 99%
“…It is therefore important to review the correlation between expansion speed and luminosity found by de Vries et al (2009). The expansion speed we determine here for CORALZ J083139+460800, exceeds the previously derived upper limit, but is still the lowest expansion speed measured in any GPS radio source so far.…”
Section: Expansion Velocity and Radio Powersupporting
confidence: 40%
“…At the time, selection effects of the available surveys were hiding the low-luminosity population of radio sources. More recent surveys of low-luminosity sources (e.g., de Vries et al 2009, Kunert-Bajraszewska et al 2010) have revealed a number of sources distributed throughout the diagram. A classification adapted to the new scenario revealed by low-luminosity observations has been proposed by An & Baan (2012), including predicted tracks depending on the initial power of the source and the activity period of the active galactic nucleus (AGN).…”
Section: Introductionmentioning
confidence: 99%